Analisis Kepuasan Pasien Bersalin Terhadap Pelayanan Kebidanan Di Ruang VK RSUD Cimacan : Analysis of Satisfaction of Maternity Patients with Midwifery Services in the VK Room of Cimacan Hospital - Romdhana, Alice; Dewi, S.ST, M.Kes, Meinasari Kurnia (Dohara POAJ, 2023)
Introduction: The results of the Community Satisfaction Survey at Cimacan Hospital in 2020 were 77,26. Meanwhile, the Community Satisfaction Survey Data for 2021 Cimacan Hospital obtained a value of 80,57; Observing the results of the survey there is an interesting thing, namely the average value of the Complaint handling element, meaning that even though the value of community satisfaction in handling complaints is the highest, there is an element of